2009
DOI: 10.1158/0008-5472.can-08-3030
|View full text |Cite
|
Sign up to set email alerts
|

Host-Derived Angiopoietin-2 Affects Early Stages of Tumor Development and Vessel Maturation but Is Dispensable for Later Stages of Tumor Growth

Abstract: The angiopoietin/Tie2 system has been identified as the second vascular-specific receptor tyrosine kinase system controlling vessel assembly, maturation, and quiescence.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
119
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(143 citation statements)
references
References 47 publications
18
119
3
Order By: Relevance
“…4B), suggesting that vascular growth and proliferation are of great importance in establishing early tumor growth. This is in agreement with recent findings where vascular growth was attributed to tumorigenicity only during the early stages of tumor growth (60,61). Furthermore, immunohistochemistry results from human lung tumors showed that A 2A receptor expression was increased mainly in the tumor stroma, a region actively involved in new blood vessel recruitment to support tumor growth.…”
Section: Discussionsupporting
confidence: 92%
“…4B), suggesting that vascular growth and proliferation are of great importance in establishing early tumor growth. This is in agreement with recent findings where vascular growth was attributed to tumorigenicity only during the early stages of tumor growth (60,61). Furthermore, immunohistochemistry results from human lung tumors showed that A 2A receptor expression was increased mainly in the tumor stroma, a region actively involved in new blood vessel recruitment to support tumor growth.…”
Section: Discussionsupporting
confidence: 92%
“…Tie2 shedding is enhanced in diseases characterized by angiogenesis or vascular remodeling [39]. Although the pathophysiologic correlation of elevated sTie2 in hematologic malignancies has not been elucidated, most authors consider the endothelial cell-derived sTie2 receptor and its circulating ligand Ang-2 as indicators for the extent of tumor-driven neoangiogenesis [30,44,45]. Accordingly, we found high levels of sTie2 in HSCT patients, suggesting ongoing Tie2 shedding.…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, the Ang2-specific peptide body inhibits tumor growth to approximately the same extent as a dual anti-Ang1/Ang2 peptide body (Oliner et al 2004;Coxon et al 2010). Providing further support for the role of Ang2 in tumor growth, tumors implanted into Ang2 KO mice grew more slowly than those implanted into wild-type mice (Nasarre et al 2009). …”
Section: Ang2 Plays a Role In Tumor Angiogenesis And Growthmentioning
confidence: 92%